CONSIDERATION OF PAVEMENT TYPE SERVICE LIFE CAPACITY FOR SUSTAINABLE INFRASTRUCTURE DEVELOPMENT IN NIGERIA - Samuel Olugbenga Abejide; Jacob Adebayo Adedeji; Moamed Mostafa (Journal of Construction Project Management and Innovation)
The opposition over the use of concrete pavement against the conventional flexible pavement in Nigeria cannot be overemphasized; nevertheless, the question of interest should be: is concrete pavement now a way out of Nigeria road network? Certainly, the success of any road pavement design practice is a function of various factors put together. Yet, the pros and cons of concrete pavement should not be seen from the perspective of a political drive but rather seen on the feasibility of achieving a reliable and sustainable pavement during the intended service life. The necessary factors to be considered in the success of pavement design will depend on; the environmental condition, geotechnical properties of the concrete pavement materials, the mix design of the concrete, the construction practice/workmanship, the expected load cycles and social acceptability. Furthermore, the emphasis on concrete pavement should be as a result of positive success already in use and the viability of the use of concrete pavement over flexible pavement will rely on successes and failures in design and construction which will depend on laboratory testing data so as to generate a code of practice manual which is suitable for a particular geographic location; since soil properties and environmental condition lies in its abundant complexity over a given location. This paper focuses on providing a guide to the use of concrete pavement design in Nigeria and how success in transforming Nigerian roads to rigid pavement can be achieved especially in failed road sections within the southern region and other regions prone to excessive rainfall precipitation.